Comparative Precision and Bias of Five Different Ageing Methods for the Large Tropical Snapper Lutjanus johnii - R. MARRIOTT (Asian Fisheries Science, 2000)
Five common methods of age determination were compared to determine their usefulness in monitoring the catch structure of a small Australian sportfishery for Lutjanus johnii. Presumed annuli were visible on scales, whole otoliths, sectioned otoliths, whole vertebrae and sectioned vertebrae of Lutjanus johnii in a sample of 44 younger fish up to 793 mm FL and 12+ years of age. An inexperienced reader produced estimates of age with acceptable levels of precision after three replicate counts using all these methods with the exception of scale reading. The most precise methods used whole otoliths, sectioned vertebrae and sectioned otoliths. Linear comparisons showed promise for calibration of results from whole and sectioned otoliths, and sectioned otoliths and whole and sectioned vertebrae, for fish less than half the known longevity of the species. However, examination of the relative position of presumed annuli and tetracycline marks showed bias and underestimation of fish age in the interpretation of the margins of vertebral centra. Comparison of the scale and otolith readings amongst experienced and inexperienced readers revealed systematic bias in the interpretation of the position of presumed annuli for fish less than 3+. It was concluded that sectioned otoliths provide the best method to determine the age of Lutjanus johnii.